VD_FINDINFO Jug / 2025 / 112 vom 20. Februar 2024 - VD Tribunal cantonal (2024)
CONSTATATION DES FAITS, FIXATION DE LA PEINE, BRIGANDAGE, AGGRAVATION DE LA PEINE, CRUAUTÉ | 140 ch. 3 CP, 140 ch. 4 CP, 47 CP, 49 al. 1 CP, 10 CPP (CH)